The Interplay of Religious and Nonreligious Meaning-Making on Psychological Well-Being in Gastrointestinal Cancer Patients - Krok, Dariusz (The international journal for the psychology of religion, 2021)
Previous research has identified close relationships between religious and nonreligious factors and well-being in cancer patients. This study expands on such studies by examining the interplay of religious and nonreligious meaning-making factors on psychological well-being in gastrointestinal cancer patients; 317 patients (160 women and 157 men) with gastrointestinal cancer participated in the current study. Two coping strategies were utilized: negative religious coping and meaning-focused coping. These mediated the relationship between the religious meaning system and psychological well-being and the relationship between the presence of meaning in life and psychological well-being. In contrast, the association between changes in beliefs and goals and psychological well-being was mediated by negative religious coping and the presence of meaning in life. Positive religious coping did not play a mediating role in the above relationships. The findings suggest that for cancer patients, religious and nonreligious factors do not exist in “a psychological vacuum” as separate entities, but tend to interact with each other on a basis of meaning structures.